Strategies for Developing Human Resources for Teachers and Students at Daarul Uluum Islamic Boarding School, Campus 2 Nagrak - Adnan, Siti Nurkhofipah; Agung, Syahrum; Avessina, Muhammad Jibriel (INOVATOR, 2024)
This research aims to find out "Human Resource Development Strategies for Teachers and Students at the Daarul Uluum Islamic Boarding School Campus 2 Nagrak". This research is a type of qualitative research. This research method is used by means of observation, interviews and documentation of the research object in a scientific and natural manner. The results of the study show that in the Daarul Uluum Islamic Boarding School Campus 2 Nagrak, the use of transformational and democratic leadership styles dominates in an effort to motivate and inspire students based on Islamic values. Teachers use a variety of teaching methods and disciplinary approaches to create an effective learning environment. The ongoing teacher training program aims to improve pedagogical abilities and character, while students are encouraged to develop leadership through a variety of extracurricular and organizational activities. Character education, discipline and creativity development are the main focus in shaping independence and leadership qualities in students. The teaching method involves mentoring, classes, and lectures, with the teacher as the main role model. Student motivation is enhanced through positive interaction, rewards and effective communication. Discipline is carried out through attendance and time management, while the recruitment of educators emphasizes the characteristics of the Prophet Muhammad PBUH and academic qualifications. In addition, the placement of teachers is adjusted to the needs of Islamic boarding schools. And entrepreneurship programs are also held for students, practicing practical skills such as handicrafts and cooking.